The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s10533-004-0364-y
|View full text |Cite
|
Sign up to set email alerts
|

The importance of in-stream uptake for regulating stream concentrations and outputs of N and P from a forested watershed: evidence from long-term chemistry records for Walker Branch Watershed

Abstract: Long-term, weekly measurements of streamwater nitrogen and phosphorus concentrations in the West Fork of Walker Branch, a 1st order forested stream in eastern Tennessee, were used to assess the importance of in-stream processes for controlling stream concentrations and watershed exports. Over the period from 1991 to 2002, there was a slight declining trend in watershed export of dissolved inorganic N via streamflow, despite relatively high and constant wet N deposition rates (5 kg/ha/y). The watershed retains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
131
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 55 publications
6
131
1
1
Order By: Relevance
“…We recognize that lab assays of nitrification and denitrification were measured under optimum redox conditions, but note that inorganic N availability represented ambient conditions. Additionally, whole-stream NO { 3 uptake may be underestimated because we used short-term nutrient additions that increased NO { 3 concentrations and thus could have saturated demand (Mulholland et al 2002). Therefore, comparing these rates represents a maximum estimate of the contribution of nitrification and denitrification to whole-stream NO { 3 dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recognize that lab assays of nitrification and denitrification were measured under optimum redox conditions, but note that inorganic N availability represented ambient conditions. Additionally, whole-stream NO { 3 uptake may be underestimated because we used short-term nutrient additions that increased NO { 3 concentrations and thus could have saturated demand (Mulholland et al 2002). Therefore, comparing these rates represents a maximum estimate of the contribution of nitrification and denitrification to whole-stream NO { 3 dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Although we calculate assimilatory U 2NO3 as the fraction of total NO { 3 removal not accounted for by denitrification, this fraction may not be solely attributable to assimilatory demand. Other processes, such as dissimilatory NO Long-term fate of assimilated N-Although assimilatory N uptake is only temporary, it slows the downstream flux of NO { 3 by removing it from the water column and transforming it into a particulate organic form (Mulholland 2004). Previous studies have rarely considered the ultimate fate of this assimilated N, but a synthesis of denitrification studies indicates the removal of assimilated N following remineralization and coupled nitrification/ denitrification when water residence times are long (Seitzinger et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al (2004) developed a watershed mass balance for the Ipswich River basin and determined that the stream network retained 9% of the total N entering the river. Mulholland (2004) found that a 300-m reach of Walker Branch, Tennessee, decreased annual NO 3 2 and PO 4 32 inflow by 20 and 30%, respectively. Several reaches of the Neversink River, New York, were a yearround net sink for NO 3 2 , attenuating 3 to 29% of the nutrient load entering them (Burns, 1998).…”
Section: Comparability Of Nutrient Uptake Metrics To Other Streamsmentioning
confidence: 95%
“…In a study of watershed stream networks in the northeastern USA, it was estimated that 76% of the N entering the stream networks may have been permanently removed via denitrification or temporarily retained through biotic sequestration (Seitzinger et al, 2002). Alteration of nutrient concentrations by riverine processes during transport also changes the timing of nutrient delivery and the quality (coarse vs. fine particulate organic matter and organic vs. inorganic dissolved nutrients) of nutrients exported to downstream ecosystems (Meyer and Likens, 1979;Mulholland, 2004).…”
mentioning
confidence: 99%
“…In-stream processes influence the transport, retention, and removal of N from the landscape (Peterson et al 2001;Mulholland 2004;Bernhardt et al 2005). Within the context of larger river networks, low-order streams can have a disproportionately large impact on the rate at which N is retained and attenuated within streams (Alexander et al 2000).…”
Section: Introductionmentioning
confidence: 99%